Performance of Armoured Steel Plate against High-Speed Projectile using Finite Element Analysis and Lab Experiment - Pathak, Sunil; Chaulagain, Raj Kumar (Journal of Advanced College of Engineering and Management, 2026)
A comprehensive understanding of the mechanical behavior of armored plates used in defense sectors under high-velocity impact is fundamental in optimizing material selection and design for specific operational requirements. This research investigates the ballistic performance of armoured steel plate through integrated finite element analysis and experimental testing. The study began with the mechanical property characterization of the armoured steel plate, from which Johnson-Cook (JC) constitutive parameters were derived by correlating with established literature. Using a finite element analysis explicit dynamic solver for the simulation of multiple impact scenarios, with simulation predictions validated against experimental test data. The experimental data of high-velocity impact from a leaded projectile at 300, 600, and 900 incident angles correlated closely with the simulation of impact on Armox 500 armoured plate, with a maximum deviation of 8.5%. Following validation, an optimized material model was implemented to further assess the armoured plate's ballistic resistance. The findings provide valuable insights into the resistance capabilities of the armoured plate, which can contribute to the defense sector.